Rancang Bangun Aplikasi Document Management System pada Bagian Persediaan di PT. Indonesia Indah Tobacco Citraniaga - Sulaiman, Jeff Edwin; sulistiowati, sulistiowati; maulana, yoppy mirza (Jurnal JSIKA, 2014)
PT . Indonesia Indah Tobacco Citraniaga (PT IITC ) is a company engaged in the tobacco industry . Currently, the company is still using a document management system that has not been good. Thats because many approval processes , delivery , storage and retrieval of documents is performed by the manual system. This problem causes a lot of wasted time, there is accumulation of the document file and document approval process is often hampered. Based on these problems , the solutions that can be offered is to design and build a document management system application in the inventory at PT . IITC which can assist users in searching , approving , storing and sending documents. This application can be used to well in the companys internal environment. Results from the testing showed that this application can facilitate the search for documents with full text indexing system and store documents electronically. In addition , this application is able to send documents electronically because of that the courier and fax machines are not needed anymore.Keywords : document management system, application, inventory